RELATIONSHIP BETWEEN GESTATIONAL AGE, PARITY, SEZ STATUS, AND ANEMIA HISTORY OF PREGNANT WOMEN IN CIAMPEL SUB DISTRICT - Qillah, Itta; Sefrina, Linda Riski; Elvandari, Millyantri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Anemia, especially in pregnant women, is a major problem for global health. Anemia is also known as iron nutritional anemia, a condition where the mother has a hemoglobin level below 11 grams/dl. The purpose of this study was to determine the relationship between maternal age, parity and SEZ status with anemia history of pregnant women in Ciampel District, Karawang Regency. This research method is a correlative analytic research with a cross sectional design. The place of research implementation in Ciampel District, Karawang Regency, with a population of 30 pregnant women. The sampling technique used sampling techniques with data collection techniques through questionnaires. The results of research on maternal age and parity with anemia history of pregnant women obtained insignificant results with a p-value of 1.000 (p>0.05) and a p-value of 0.210 (p>0.05), while the results of research on SEZ status obtained a significant value with a p-value of 0.001 (p<0.05). The conclusion of this study shows that there is a significant relationship between SEZ status and the incidence of anemia in pregnant women, while the relationship between maternal age and parity has no significant relationship with the history of anemia in pregnant women.